Trindade-Goiás, partida e repartida: a dinâmica urbana de um território fragmentado - Rodrigues, Wildes Jesus (2021)
The analysis of urban space is complex and there are several methodologies that seek, together with each other, to approach the understanding of its reality. Urban dynamics is an element present in the city and, in this research, we carry out this approach based on the analysis of what we mean by fragmented territory. Trindade, in the state of Goiás, was the site of this analysis due to the fact that this municipality has two urban networks with different particularities: Trindade II and the seat of the municipality. The first, close to the capital of the state of Goiás, Goiânia, and the other distant approximately 16 kilometers from the referred capital. Trindade II has the particularity of a training process directly linked to Goiânia and faces the challenges of urbanization, far from the central nucleus of the municipality. Elsewhere, the seat of the municipality is located, directly linked to a Catholic tradition and the growing influence of religious tourism. The purpose of this investigation was to analyze the urban dynamics to understand the city of Trindade and its functions. What is Trindade? How is the territorial dynamics of a fragmented city? What are the effects on the social, cultural and political field generated by the territorial fragmentation of Trindade? To understand and answer these questions, a brief survey was carried out on the territorial formation of the city of Trindade and the constitution of Trindade II. Several data were analyzed, from secondary sources, referring to population growth, migration, industrialization and services. In order to analyze the city of Trindade, it was necessary to understand the power relations that operated and operate in its territory and, next, to inquire about the reflexes of fragmentation, in Trindadan territory. We demonstrate that territorial fragmentation is present in the daily life of the city and that it has direct effects on local politics. We also show that the city of Trindade has economic autonomy, with emphasis on the service sector, but many of its citizens are dependent on Goiânia.